2017
DOI: 10.1002/ijc.30722
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to nutrition‐based cancer prevention guidelines and breast, prostate and colorectal cancer risk in the MCCSpain case–control study

Abstract: Prostate, breast and colorectal cancer are the most common tumours in Spain. The aim of the present study was to evaluate the association between adherence to nutrition-based guidelines for cancer prevention and prostate, breast and colorectal cancer, in the MCC-Spain case-control study. A total of 1,718 colorectal, 1,343 breast and 864 prostate cancer cases and 3,431 population-based controls recruited between 2007 and 2012, were included in the present study. The World Cancer Research Fund/American Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 27 publications
8
63
4
2
Order By: Relevance
“…For example, an Italian case–control study found that the subjects in the highest category of the WCRF/AICR score had 30% reduced CRC risk in comparison to those in the lowest category . Another Spanish case–control study found that one‐point increment in the WCRF/AICR score was associated with 25% lower CRC risk . The EPIC study concluded that a one‐point increment in the WCRF/AICR score was associated with 12% reduced CRC risk .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an Italian case–control study found that the subjects in the highest category of the WCRF/AICR score had 30% reduced CRC risk in comparison to those in the lowest category . Another Spanish case–control study found that one‐point increment in the WCRF/AICR score was associated with 25% lower CRC risk . The EPIC study concluded that a one‐point increment in the WCRF/AICR score was associated with 12% reduced CRC risk .…”
Section: Discussionmentioning
confidence: 99%
“…The results from this analysis in Morocco are in line with several other studies that have investigated the association of adherence to the WCRF/AICR recommendation 30 with cancer risk. 9,14,[17][18][19] For example, an Italian case-control study found that the subjects in the highest category of the WCRF/AICR score had 30% reduced CRC risk in comparison to those in the lowest category. 19 Another Spanish case-control study found that one-point increment in the WCRF/AICR score was associated with 25% lower CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…A WCRF/AICR score was constructed, incorporating six recommendations for cancer prevention (body fatness, physical activity, foods and drinks that promote weight gain, plant foods, animal foods and alcoholic drinks). 28 The total WCRF/ AICR score ranged from 0 to 6, with higher scores indicating greater adherence to the WCRF/AICR recommendations. The score was further categorized into sex-specific tertiles according to the distribution of the score in controls.…”
Section: Data Collectionmentioning
confidence: 99%
“…The World Cancer Research Fund (WCRF) and the American Institute for Cancer Research (AICR) have released evidence‐based recommendations for cancer prevention related to adiposity, physical activity and diet . Overall adherence to the WCRF/AICR recommendations has in several studies been linked to lower risk of cancer morbidity and mortality . There are several nonmodifiable risk factors that may affect an individual's risk of cancer, including genetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Overall adherence to the WCRF/AICR recommendations has in several studies been linked to lower risk of cancer morbidity and mortality. [7][8][9][10][11][12][13][14][15] There are several nonmodifiable risk factors that may affect an individual's risk of cancer, including genetic susceptibility. The potential benefit of adherence to a healthy lifestyle in these subjects is not known.…”
Section: Introductionmentioning
confidence: 99%